A low-cost, easy-to-use prototype bioreactor model for the investigation of human gut microbiota: validation using a prebiotic treatment - Agrinier, Anne-Laure; Pilon, Geneviève; Marette, André (Frontiers in Microbiology, 2024)
In vitro gut models allow for the study of the impact of molecules on human gut microbiota composition and function without the implication of the host. However, current models like Simulator of Human Intestinal Microbial Ecosystem (SHIME ®) are expensive, time-consuming, and require specialized personnel.Homemade in vitro models, that lessen these issues, have limited evidence of their humanlike functionality.Here, we present the development of a low-cost and easy-to-use bioreactor with proven functionality of human microbiota. In our model, we evaluated the capability of replicating human gut microbiota growth and the response of the human bacterial community to a prebiotic, resistant starch type 2 (RS2). Our bioreactor produced an environment found to be stable for pH, temperature, and anaerobic conditions. The bioreactor consistently cultivated bacterial communities over a 48h time-period, replicating the composition of the gut microbiota and the associated metabolite production response to RS2, in line with prior human study. In response to the RS2 prebiotic, we observed an increased increases in Bifidobacterium adolescentis and Bifidobacterium faecale and increased production of the short-chain fatty acids acetate, propionate, and isobutyrate. Taken together, these data demonstrate that our low-cost and user-friendly prototype of bioreactor model provides a favorable environment for the growth of human gut microbiota and can mimic its response to a prebiotic.